2005
DOI: 10.1038/oby.2005.72
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Reference Genes for Studies of Gene Expression in Human Adipose Tissue

Abstract: Research Methods and Procedures:Using 52 human adipose tissue expression profiles (HU95), 10 putative reference genes with the lowest variation in expression levels were selected for further studies. Expression stability of these 10 novel and 5 previously established reference genes was evaluated by real-time reverse transcriptase-polymerase chain reaction analysis. For this purpose, 44 adipose tissue biopsies from 27 subjects were chosen to include a wide range of parameters such as sex, age, BMI, depot origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 13 publications
4
122
0
Order By: Relevance
“…Amplification efficiencies were validated and normalized to ribosomal 18S and quantity of target gene was calculated according to a standard curve. 18S is an established and accepted reference gene (14). Our own experience showed that it is comparable with other reference genes including LRP10, CLN3, and HPCAL1 (data not shown).…”
Section: Zfp36 Measurementsmentioning
confidence: 69%
“…Amplification efficiencies were validated and normalized to ribosomal 18S and quantity of target gene was calculated according to a standard curve. 18S is an established and accepted reference gene (14). Our own experience showed that it is comparable with other reference genes including LRP10, CLN3, and HPCAL1 (data not shown).…”
Section: Zfp36 Measurementsmentioning
confidence: 69%
“…C t values were normalized to the reference gene, low-density lipoprotein receptor-related protein 10 (LRP10), which was amplified in parallel reactions. LRP10 was preferred as a reference gene because it displayed the least variation in expression among a number of reference genes in human adipose tissue (25). RNA interference of IRS-1.…”
Section: Methodsmentioning
confidence: 99%
“…A standard curve was plotted for each primer-probe set with a serial dilution of pooled adipose tissue cDNA. Human LRP10 [29] was used as a reference to normalize the expression levels between the samples. All the standards and samples were analyzed in triplicate.…”
Section: Rt-pcr Analysismentioning
confidence: 99%